Geographical patterns of Yunnan seed plants may be influenced by the clockwise rotation of the Simao-Indochina geoblock - Hua, Zhu (Frontiers in Earth Science, 2015)
Floristic patterns of seed plants in Yunnan, southwestern China, were studied to assess the relationship between the floristic geography and geological history. A database of 38 regional floristic studies covering Yunnan was used and the patterns of seed plant distributions across these regional floras were quantified at the generic level. Genera with tropical Asian distributions are the most dominant geographical elements in the Yunnan flora. They show oblique patterns of abundance across Yunnan. They are most abundant in southern and western Yunnan, and their proportion in regional floras declines abruptly in eastern, central and northern Yunnan. The oblique abundance patterns of geographical elements in Yunnan differ from those of genera in southern and eastern China, which had a high correlation with latitudinal gradients controlled by climate. They cannot be explained by climate alone, but can be explained at least partly by the geological history. The oblique abundance patterns of Yunnan seed plants correspond well to the clockwise rotation and southeastward extrusion of the Simao-Indochina geoblock caused by the collision of India with Asia.